Factors Associated with Need for Intravenous Glucose Infusion for the Treatment of Early Neonatal Hypoglycemia in Late Preterm and Term Neonates - Brion, Luc P.; Scheid, Lisa M.; Brown, L Steven; Burchfield, Patti J.; Rosenfeld, Charles R. (American Journal of Perinatology, 2023)
Objective The aim of this study was to determine which late-preterm (35–36 weeks' gestational age [GA]) and term neonates with early-onset hypoglycemia in the first 72 hours postnatal required a continuous glucose infusion to achieve and successfully maintain euglycemia.Study Design This is a retrospective cohort study of late preterm and term neonates born in 2010–2014 and admitted to the Mother-Baby Unit at Parkland Hospital who had laboratory-proven blood glucose concentration < 40 mg/dL (2.2 mmol/L) during the first 72 hours of life. Among the subgroup needing intravenous (IV) glucose infusion, we analyzed which factors predicted a maximum glucose infusion rate (GIR) ≥ 10 mg/kg/min. The entire cohort was randomly divided into a derivation cohort (n = 1,288) and a validation cohort (n = 1,298).Results In multivariate analysis, the need for IV glucose infusion was associated with small size for GA, low initial glucose concentration, early-onset infection, and other perinatal variables in both cohorts. A GIR ≥ 10 mg/kg/min was required in 14% of neonates with blood glucose value < 20 mg/dL during the first 3 hours of observation. The likelihood of a GIR ≥ 10 mg/kg/min was associated with lower initial blood glucose value and lower umbilical arterial pH.Conclusion Need for IV glucose infusion was associated with small size for GA, low initial glucose concentration, early-onset infection, and variables associated with perinatal hypoxia–asphyxia. The likelihood of a maximum GIR ≥ 10 mg/kg/min was greater in neonates with lower blood glucose value during the first 3 hours of observation and lower umbilical arterial pH.Key Points
Keywords: hypoglycemia; late preterm; term; glucose infusion rate; prediction